The Role of Training in Basketball Concentration for Elementary Schools: Peran Latihan Konsentrasi Bola Basket untuk Sekolah Dasar - Ramadhan, Muhammad Naufal (Pedagogia : Jurnal Pendidikan, 2019)
This study aims to get results about the role of elementary school level concentration training in basketball athletes, because what happens in the field at a very young age they experience psychological disabilities so that they experience less focus during competition, problems must be analyzed so that the results can provide psychological improvement to children especially at the level of concentration of athletes. This study uses a quantitative method that uses an instrument of grid concentration training and free throw with the athlete's implementation procedure to carry out concentration accompanied by a tester, a scoring system carried out with the total number of numbers mentioned minus the number of consecutive numbers that must be sorted. the results showed an increase from eight trials in 30 athletes with an average increase of 60%, before 20.80-26.57. It can be concluded that grid exercises and free throw tests can be used to increase concentration at the elementary school level